2022
DOI: 10.3847/1538-4357/ac63be
|View full text |Cite
|
Sign up to set email alerts
|

NICER Monitoring of Supersoft X-Ray Sources

Abstract: We monitored four supersoft sources—two persistent ones, CAL 83 and MR Vel, and the recent novae YZ Ret (Nova Ret 2020), and V1674 Her (Nova Her 2021)—with NICER. The two persistent supersoft X-ray sources (SSS) were observed with unvaried X-ray flux level and spectrum, respectively, 13 and 20 yr after the last observations. Short-period modulations of the SSS appear where the spectrum of the luminous central source was fully visible (in CAL 83 and V1674 Her) and were absent in YZ Ret and MR Vel, in which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
(92 reference statements)
2
5
0
Order By: Relevance
“…The WD photosphere is occulted by the edge of an elevated accretion disk (e.g., Ness et al 2013;Sokolovsky et al 2022). It is consistent with the small X-ray fluxes during the SSS phase (see also Orio et al 2022); the flux at the SSS phase is about 10 times smaller than that at the X-ray flash phase on t 0 + 0 days (filled red square in Figure 1). Izzo et al (2020) observed YZ Ret with the UVES at ESO on t 0 + 72 days (JD 2,459,110.5) in the mid-SSS phase.…”
Section: Soft X-ray Emissionsupporting
confidence: 72%
“…The WD photosphere is occulted by the edge of an elevated accretion disk (e.g., Ness et al 2013;Sokolovsky et al 2022). It is consistent with the small X-ray fluxes during the SSS phase (see also Orio et al 2022); the flux at the SSS phase is about 10 times smaller than that at the X-ray flash phase on t 0 + 0 days (filled red square in Figure 1). Izzo et al (2020) observed YZ Ret with the UVES at ESO on t 0 + 72 days (JD 2,459,110.5) in the mid-SSS phase.…”
Section: Soft X-ray Emissionsupporting
confidence: 72%
“…A remarkable feature of V1674 Her is the emergence of orbital (3.67 h = 0.153 d; Schmidt et al 2021) and white dwarf spin periods (8.36 min = 0.00580 d; Patterson et al 2021) shortly after the eruption. The two periods are seen in X-rays in addition to optical data (Maccarone et al 2021;Pei et al 2021;Page et al 2022;Orio et al 2022a;Lin et al 2022). The spin period was present before the eruption according to the Zwicky Transient Facility photometry reported by Mroz et al (2021).…”
Section: V1674 Her -Nova Herculis 2021mentioning
confidence: 86%
“…The spin period change may be caused by some combination of magnetic coupling between the rotating white dwarf and the ejecta, non-rigid rotation or substantial radial expansion of the heated white dwarf. Following the spin-down associated with the eruption, a spin-up in the post-eruption phase is reported by (Patterson et al 2022) on the basis of optical photometry, while the presence of changes in the X-ray derived period deserves further investigation (Drake et al 2021;Orio et al 2022a).…”
Section: V1674 Her -Nova Herculis 2021mentioning
confidence: 99%
See 1 more Smart Citation
“…We searched for periodic signals that could be associated with the rotation period of the X-ray source (hundreds of milliseconds to tens of seconds); alternatively, to identify flux modulations of the order of tens of seconds to hours as observed in novae and supersoft X-ray sources (Orio et al 2022). We considered only the two ∼ 30 ks XMM-Newton observations of J0221 (Table 2), the individual eRASS exposures being too shallow for a meaningful timing analysis.…”
Section: Timing Analysismentioning
confidence: 99%